Penyalahgunaan Obat Psikofarmaka dan Dampaknya terhadap Kesehatan Mental Remaja di Sekolah Menengah Atas (SMA) - Syifa’, Nailis; Aprilia, Galuh; Risqi, Iin Hiqmathul; Agustin, Nesha Elcyra; Mirza, Mazaya Febinazhira; Hasan, Qurrotul Aini; Safitriana, Laela Jelita; Fikriyah, Izzatul; Fazha, Nurliva Maulidya; Syafira, Kholifah; Aulia, Nazhirah Rahma (Jurnal Pengabdian Nasional (JPN) Indonesia, 2025)
High school students often experience pressures that affect their mental health due to unstable personalities. The negative effects of poorly managed mental health can impact their development. Therefore, early education on the abuse of psychopharmaceutical drugs and its impact on adolescent mental health is essential. The specific target of this counseling activity was to enhance the understanding of students at Muhammadiyah 3 Batu High School. The method used involved delivering materials and explanations through a PowerPoint presentation and the "tree of hope" activity, making it easier for students to comprehend the content. The results of this counseling indicated an increase in student knowledge and understanding. Pre-test results showed that 95.24% of students understood the material well, 3.17% understood sufficiently, and 1.59% lacked understanding of the abuse of psychopharmaceutical drugs and its relation to mental health. After the information session (post-test), 96.83% of students demonstrated a strong understanding, and 3.17% understood sufficiently. Overall, this counseling activity has the potential to improve student understanding and engagement on the relationship between the abuse of psychopharmaceuticals and mental health.